Tract(atus) 23: La théorie est attente - Grelet, Gilles (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Gilles Grelet Title (French): Tract(atus) 23: La théorie est attente Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 108 Page Count: 1 Citation (English): Gilles Grelet, “Tract(atus) 23: La théorie est attente,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 108.